Adam Smith and the Human Stomach - Davis, Joseph S. (Quarterly Journal of Economics, 1954)
I. Adam Smith and man's wants, 275. — II. Extent to which wants for food are satiated, 276. — III. Relation of the capacity of the human stomach to satiation of wants for food, 278. — IV. Variations in economic cost of various diets, 280. — V. Relation of wants for food to wants for other consumer goods, 281. — VI. Factors of importance in determining the population a country can feed, 283. — VII. Conclusion, 285.